Analisis Strategi Customer Relationship Management sebagai Upaya Mempertahankan Loyalitas Pelanggan dalam Pembelian Produk UMKM di Kecamatan Medan Tembung - Adinda Sefina; Nuri Aslami; Muhammad Irwan Padli Nasution (Jurnal Riset Akuntansi, 2026)
This study aims to analyze Customer Relationship Management (CRM) strategies as an effort to maintain customer loyalty in purchasing UMKM products. This research employs a descriptive qualitative method with data collection techniques conducted through observation and interviews. The collected data were analyzed using SWOT analysis to identify internal and external factors related to customer relationship management strategies. The results provide strategic recommendations for UMKM Jangek Berkah and Sate Padang Ajo Faisal to optimize customer data management, including information from non-regular customers, as these customers have the potential to develop into loyal customers in the future. Furthermore, the findings emphasize the importance of continuous product innovation and effective marketing strategies to strengthen competitiveness in an increasingly competitive market. The implementation of CRM strategies enables UMKM to build stronger relationships with customers, improve customer retention, and create sustainable business growth. This study contributes practical insights for UMKM managers in utilizing customer relationship strategies to enhance loyalty and maintain competitive advantage.